2016
DOI: 10.4168/aair.2016.8.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled NO: Determinants and Clinical Application in Children With Allergic Airway Disease

Abstract: Nitric oxide (NO) is endogenously released in the airways, and the fractional concentration of NO in exhaled breath (FeNO) is now recognized as a surrogate marker of eosinophilic airway inflammation that can be measured using a noninvasive technique suitable for young children. Although FeNO levels are affected by several factors, the most important clinical determinants of increased FeNO levels are atopy, asthma, and allergic rhinitis. In addition, air pollution is an environmental determinant of FeNO that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 71 publications
1
43
1
2
Order By: Relevance
“…Determinants of exhaled NO includes age, sex, body height, atopy and smoking status,19,33 but in our study exhaled NO correlates only with age, and in spite of a significant correlation, it is weak and was not possible to derive any equation of reference values (results not shown). In developing individuals, exhaled NO increases until 14 years in females and 16 in males, and similar development is observed for anatomic dead space volume.34 This finding suggests that the growth dependency in exhaled NO levels…”
contrasting
confidence: 61%
See 1 more Smart Citation
“…Determinants of exhaled NO includes age, sex, body height, atopy and smoking status,19,33 but in our study exhaled NO correlates only with age, and in spite of a significant correlation, it is weak and was not possible to derive any equation of reference values (results not shown). In developing individuals, exhaled NO increases until 14 years in females and 16 in males, and similar development is observed for anatomic dead space volume.34 This finding suggests that the growth dependency in exhaled NO levels…”
contrasting
confidence: 61%
“…Secondly, our evaluations were conducted during pollen season, contributing to high exhaled NO levels, even when asthma was not present, in pollen allergic patients. 19 Thirdly, the use of respiratory symptoms The ability of exhaled NO to identify asthma in children has shown conflicting results; a cut-off value of 19 ppb has been suggested, with a sensitivity and specificity of 91% and 87%, respectively, for diagnosing mild asthma. 20 This was partially supported by a large real-life study of school aged children, where levels of exhaled NO above 15.8 ppb showed to be reliable to identify asthma.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with results from numerous studies that reported higher FeNO levels in allergic than non-allergic subjects, in both children and adults. 17,18 Furthermore, a previous study found that perennial allergic rhinitis was associated with high FeNO levels and more severe asthma. 19 In our study, the subjects were younger in the high FeNO group compared with the normal group, which may be due to a higher prevalence of allergies in younger compared with the older age groups.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that there were significant disorders in nitric oxide (NO) related metabolism before and after treatment, including arginine and proline metabolism, tyrosine metabolism, and nitrogen metabolism. NO acts as an inflammatory mediator in the airway (Kim et al, 2016). NO imbalance is considered to play an important role in the pathogenesis of allergic rhinitis, and nasal NO has been proved to be the best biomarker for distinguishing AR from non-AR (Takeno et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…NO is synthesized from L-arginine by nitric oxide synthase, which also plays an important role in the pathophysiology of rhinitis, especially in the glandular function of allergic nasal mucosa (Kang et al, 2000). Nitric oxide synthase is expressed in many cell types, such as epithelial cells, inflammatory cells (macrophages, neutrophils, and mast cells), airway nerves and vascular endothelial cells (Kim et al, 2016). The recruitment of eosinophils is accompanied by an increase in NO in the nasal cavity, which leads to oxidative stress (Hanazawa et al, 2000).…”
Section: Discussionmentioning
confidence: 99%